Developing the Pedagogical Skills of Prospective Teachers for Teaching Languages in an Intercultural Kindergarten Environment - Minkova Topolska, Evgenia (Acta Paedagogica Vilnensia, 2017)
Language learning is a prerequisite for successful intercultural communication. Learning the official language of a country is of significant importance for this process as well as for learning English, which is a globally accepted language in the international community. The training of students, prospective teachers, to work in an intercultural environment includes a complex development of linguistic, pedagogical and intercultural competence. This article is dedicated to developing student teachers’ pedagogical skills in teaching the official language of a country (Bulgarian language in this case) as part of their overall training in intercultural education. The theoretical part contains a brief analysis of specialized linguistic, pedagogical and methodological literature as well as an analysis of preschool education programs in the Republic of Bulgaria.